Repercussões do tratamento medicamentoso para o paciente com hepatite C crônica - Oliveira, Daniela Maria Falcão de (2012)
Hepatitis C is a major cause of chronic liver disease worldwide. It is currently estimated that there are between 2% and 3% infected people in the world, representing from 123 million to 170 million people. One also must account for this disease progressing to cirrhosis and hepatocellular carcinoma. Drug treatment, clinical follow-up, and uncertain prognosis of this disease usually give rise to adversities, which destabilize its patients daily routines and compromise their quality of life. Only after the first treatment can the person actually feel ill. Therefore, it is important to understand the impact of this phenomenon on patients. Goals: To understand chronic hepatitis C patients perceptions, meanings, and feelings about the disease treatment and its repercussions on their everyday life. Methods: During this research, of a qualitative nature, twelve patients being treated for chronic hepatitis C were interviewed at the Viral Hepatitis Clinic in São Carlos, Brazil. The final size of the sample was determined by theoretical saturation. The data were analyzed by means of content analysis technique (enunciation analysis) so as to grasp the meanings of expressions and feelings contained in the participants statements. Results: As regards the interviewees, there was a predominance of females (nine women and three men), all São Carlos residents. Their average age was 49 years, ranging from 35 to 65. As to the participants marital status, most of them (9) were married. Regarding their schooling, most patients (8) had studied 8-12 years. As for their occupation, two were retired and two were on a sick leave as a result of adverse treatment events. The data generated by the semi-structured questionnaire were organized into six categories encompassing both the factors mentioned by the patients and the researchers observations and inferences, namely: medication; adverse events and dispensation of medication; reactions to losses, fears, and distress; stigma and prejudice; lived sexuality; coping with their new reality. The results are discussed in light of two themes: (1) becoming sick due to treatment: perceived aspects and (2) undergoing treatment: the means to cope with it. Conclusion: The quality of Hepatitis C patients lives and daily routines is compromised by different feelings and uncertainties about the disease prognosis, especially due to adverse drug events. However, patients find ways to cope with the treatment and finish it presuming a satisfactory outcome. It is suggested that health professionals acknowledge this commitment and integrate, into their professional practices, interventions that increase patients awareness and support.